2021
DOI: 10.1111/jpn.13595
|View full text |Cite
|
Sign up to set email alerts
|

Thymol in fattening rabbit diet, its bioavailability and effects on intestinal morphology, microbiota from caecal content and immunity

Abstract: To our knowledge, no study has been carried out to evaluate the effects of thymol sustained administration on gut health and immune response in terms of its bioavailability in the rabbit organism. A total of 48 rabbits were randomly divided at 35 days of age into two dietary treatment groups (C/control or T/thymol at 0.025% addition). Thymol was added for 21 days and then withdrawn for 7 days. Thymol content in faeces (p < 0.001) and caecal content (p < 0.05) was significantly higher than in plasma during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…are two potential pathogenic bacteria frequently present in diarrheic rabbits and can lead to mortalities after weaning in excess of 20% [ 22 , 23 ]. Broadly, the term “gut health” describes the interaction between the intestinal wall barrier, the microbiota, and the immune components, which permit organisms to cope with internal and external stressors [ 24 , 25 ]. It is well known that the intestinal wall represents a natural barrier against pathogens and toxic substances present in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…are two potential pathogenic bacteria frequently present in diarrheic rabbits and can lead to mortalities after weaning in excess of 20% [ 22 , 23 ]. Broadly, the term “gut health” describes the interaction between the intestinal wall barrier, the microbiota, and the immune components, which permit organisms to cope with internal and external stressors [ 24 , 25 ]. It is well known that the intestinal wall represents a natural barrier against pathogens and toxic substances present in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous results from Gonthier et al (2003) , dietary CGA is only absorbed at a rate of approximately 33% in the small intestine, and consequently, most dietary CGA is able to reach the large intestine. Gut health often refers to interaction between the intestinal wall barrier, the microbiota, and physiological and immunological components, which enable different animals to cope with internal and external stressors ( Placha et al, 2022 ). The intestinal mucosa, serving as cellular barrier, is the primary location of interaction with external materials and bacteria ( Perez-Lopez et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the inclusion of 1% OEO in feed improved the feed conversion ratio, while dietary supplementation with OEO at a dosage of 600 mg/kg significantly reduced feed intake and improved feed conversion in livestock animals. Strkolcova et al reported significant increases in the ratio of villi height to crypt depth in the small intestinal wall of rabbits ( p < 0.01), blood phagocytic activity ( p < 0.0001), and the presence of lactic acid bacteria in the cecal appendix ( p < 0.01) and fecal lactic acid bacteria ( p < 0.05) following the discontinuation of thymol [ 72 ]. These findings provide evidence that thymol can have a positive impact on the intestinal health and immune response of rabbits, thereby enhancing the fattening ability of farmed rabbits.…”
Section: Bioactivity Of Essential Oils In Oregano Speciesmentioning
confidence: 99%